Docetaxel‐loaded solid lipid nanoparticles: a novel drug delivery system. Issue 6 (25th July 2017) - Sumera,; Anwar, Amania; Ovais, Muhammad; Khan, Abad; Raza, Abida
Abstract : Over the past few years, taxanes have emerged as a new class of anticancer drugs. Docetaxel (DTX) the prototype of this class has been approved for the treatment of broad range of cancers. However, to date the commercial preparation of DTX (Taxotere ® ) is accompanying adverse side effects, intolerance, and poor solubility, which can be overcome by encapsulating them using solid lipid nanoparticles (SLNs). SLNs represent versatile delivery system of drugs with newer forms such as polymer–solid lipid hybrid, surface modified and long circulating nanoparticles bringing forth improved prospects for cancer chemotherapy. In this review, the authors have discussed the current uses of various SLNs formulations of DTX with key emphasis on controlled and site‐specific drug delivery along with enhanced antitumour activity elucidated via in vitro and in vivo studies. Furthermore, the review article highlights few approaches that can be used in combination with existing DTX‐loaded SLNs to supplement DTX drug delivery.